M. Gorky’s Works of 1890-1900 in French Literary Criticism and Publicity of Early 20th Century: from Fact to Image - M. G. Urtmintseva; T. G. Maksimova (Научный диалог, 2019)
A review of literary-critical and journalistic articles about M. Gorky published in French periodicals of the early 20th century is made, some of which in our translation are for the first time introduced into scientific use. The purpose of the work is to determine the features of the perception of the writer’s works based on the analysis of the first responses to his works published in France. Special attention is paid to the article by E. Melchior de Vogue “Maxim Gorky. Works and personality of the writer,” in which the author analyzes Gorky’s works in the Russian and foreign context. The article analyzes the article by Pylon Edmond, a French writer and critic, in which the biographical aspect of M. Gorky’s image is correlated with the facts from the life of F. Villon. Materials about M. Gorky published in the most famous French periodicals of the early 20th century are characterized: L’Aurore, La Presse, Le Figaro, Le Temps, that have regularly published notes covering various aspects of the life of Maxim Gorky, especially his political views. As the study showed, despite the incredible popularity of Gorky in France, the majority of authors of journalistic articles perceived Gorky as a socio-political figure, a man with an exceptional biography, but not the artist of a word.